2016
DOI: 10.2501/ijmr-2016-005
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Preference and Stated vs Derived Importance Satisfaction Research

Abstract: This paper presents a case study that reveals how stakeholders in the research process, by recommending specific data collection and analytical techniques, exert significant 'hidden' influence on the decisions made on the basis of market research findings. While disagreements amongst stakeholders regarding research design are likely, the possibility that strategies adopted by companies are dependent upon stakeholder research preferences has not been adequately addressed in the literature.Two widely used quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
0
10
0
3
Order By: Relevance
“…The research found a correlation relationship between the perceived quality of the products and customer satisfaction with (t-statistics=4.943 and path weight of 0.313), and the p-value of 0.000 which implies that the hypothesis (H1) is accepted as the perceived quality of Islamic bank products significantly affect customer satisfaction and this finding is similar to that of [19], where they found that perceived quality of green products has a positive effect on customer satisfaction, and also [38] saw the same direct and positive relationship between product perceived quality and customer satisfaction in hotel industry. Though, a score of findings found a negative and indirect relationship between perceived quality of products and customer satisfaction, for instance in the findings of [58].…”
Section: Perceived Quality Towards Customer Satisfactionmentioning
confidence: 67%
See 1 more Smart Citation
“…The research found a correlation relationship between the perceived quality of the products and customer satisfaction with (t-statistics=4.943 and path weight of 0.313), and the p-value of 0.000 which implies that the hypothesis (H1) is accepted as the perceived quality of Islamic bank products significantly affect customer satisfaction and this finding is similar to that of [19], where they found that perceived quality of green products has a positive effect on customer satisfaction, and also [38] saw the same direct and positive relationship between product perceived quality and customer satisfaction in hotel industry. Though, a score of findings found a negative and indirect relationship between perceived quality of products and customer satisfaction, for instance in the findings of [58].…”
Section: Perceived Quality Towards Customer Satisfactionmentioning
confidence: 67%
“…Though quality management performance is studied in Toto, the connection between quality practices built on quality dimensions and perceptions of customers permits an added study [38,51,64]. This study starts with a review of the quality dimension and perspectives, in the literature.…”
Section: Product Qualitymentioning
confidence: 99%
“…Conhecer a satisfaçaõ em relação a cada atributo permite entender os pontos em que as expectativas dos clientes não estaõ sendo alcançadas, sendo parte importante na identificaçaõ das ações que precisam de melhorias (Matsukuma e Hernandez, 2007). Como apresentado por diversos autores (Baiaõ et al, 2011;Chu, 2002;Greenland et al, 2016;Gustafsson e Johnson, 2004;Matsukuma e Hernandez, 2007), conhecer apenas a percepçaõ dos clientes em relação aos atributos do serviço muitas vezes não é o suficiente; é tambeḿ necessário entender o quanto esses atributos influenciam no nıvel de satisfação geral. Desse modo, a importância relativa entre cada aspecto do serviço possibilita identificar os pontos mais relevantes, de forma que os esforços sejam alocados de maneira eficiente e com o objetivo de obter a satisfaçaõ do cliente.…”
Section: Qualidade Do Transporte Coletivo Por ôNibusunclassified
“…No entanto, não há um consenso claro entre os profissionais sobre a melhor forma de obter a importância e muitos autores mostraram em seus estudos que nem sempre as abordagens fornecem o mesmo resultado (Baiaõ et al, 2011;Greenland et al, 2016;Chu, 2002;Gustafsson e Johnson, 2004;Matsukuma e Hernandez, 2007).…”
Section: Determinação Da Importânciaunclassified
See 1 more Smart Citation